A system‐based intervention to reduce Black‐White disparities in the treatment of early stage lung cancer: A pragmatic trial at five cancer centers. (4th February 2019) - Cykert, Samuel; Eng, Eugenia; Walker, Paul; Manning, Matthew A.; Robertson, Linda B.; Arya, Rohan; Jones, Nora S.; Heron, Dwight E.
Abstract: Background: Advances in early diagnosis and curative treatment have reduced high mortality rates associated with non‐small cell lung cancer. However, racial disparity in survival persists partly because Black patients receive less curative treatment than White patients. Methods: We performed a 5‐year pragmatic, trial at five cancer centers using a system‐based intervention. Patients diagnosed with early stage lung cancer, aged 18‐85 were eligible. Intervention components included: (1) a real‐time warning system derived from electronic health records, (2) race‐specific feedback to clinical teams on treatment completion rates, and (3) a nurse navigator. Consented patients were compared to retrospective and concurrent controls. The primary outcome was receipt of curative treatment. Results: There were 2841 early stage lung cancer patients (16% Black) in the retrospective group and 360 (32% Black) in the intervention group. For the retrospective baseline, crude treatment rates were 78% for White patients vs 69% for Black patients ( P  < 0.001); difference by race was confirmed by a model adjusted for age, treatment site, cancer stage, gender, comorbid illness, and income‐odds ratio (OR) 0.66 for Black patients (95% CI 0.51‐0.85, P  = 0.001). Within the intervention cohort, the crude rate was 96.5% for Black vs 95% for White patients ( P  = 0.56). Odds ratio for the adjusted analysis was 2.1 (95% CI 0.41‐10.4, P  = 0.39) for Black vs White patients. Between group analyses confirmed treatment parity for the intervention. Conclusion: A system‐based intervention tested in five cancer centers reduced racial gaps and improved care for all. Abstract : A multi‐faceted intervention tested in five cancer centers using the transparency of race‐specific data feedback, real‐time warnings derived from EHRs, and patient‐centered navigation improved care for both Black and White patients while reducing racial differences. Application of this system‐based, pragmatic approach at a health system level could have positive effects on treatment completion, equity and overall outcomes.